Conjugation of nanomaterials containing rare-earth ion Tb3+ with CD133 monoclonal antibody and its potentials for labeling colon cancer cells (HT-29) - Nhat Minh, Le; Trong Nhan, Vo; Thi Nga, Nguyen; Thu Huong, Tran; Thi Kim Hue, Phung; Thi Thao, Do (Vietnam Journal of Biotechnology, 2020)
Nanotechnology is the key technology that brings many important applications in biomedical research. Nanolantanites present high stability, easy fabrication and functionalization. Tb3+ ion-containing nanomaterial, a specific type of nanolantanites, possess great prospects. In addition, cancer stem cells (CSCs) are directly related to drug resistance, metastasis, recurrent cancer, etc. Therefore, CSCs are considered as the target for cancer researching and for discovery of more effective therapies. CD133, a trans-membrane glycoprotein, is one of the typical markers that are found to appear very commonly on the surface of many types of CSCs. In this study, CD133 monoclonal antibody (MAb) was cojugated with nanomaterials containing Tb3+. The coupling between fluorescented nanomaterials containing Tb3+ ions and CD133 MAb was then incubated with human colon cancer cells (HT-29) to evaluate its ability to label CSCs in vitro. The results showed that nanorods containing rare-earth based Tb3+ ions which were fabricated by hydrothermal method, present the length of about 300 - 800 nm and the diameter in range of 40 - 50 nm. The Tb3+ nanoparticals also have hexagonal structure of terbium phosphate monohydrate and green illuminant. Tb3+ nanorods were also further surface silica coated and amino-silane functionalized. This nanostructure was successfully combined with monoclonal antibodies against CD133 which labelled the surface marker of HT-29 human colon cancer cells. As a result, the combination of CD133+TbPO4@Silica-NH2 (functionalized surface) showed stronger luminescence than the CD133+TbPO4 unfunctionalized combination.